ENHANCING ARABIC VOCABULARY LEARNING THROUGH FILL-IN-THE-BLANK SENTENCE PUZZLES: EVIDENCE FROM A QUASI-EXPERIMENTAL STUDY ON RETENTION AND LEARNER ENGAGEMENT - Ahmad Fikri; Harisah Harisah; Abdul Hafidz bin Zaid; Mukmin Mukmin; Nurul Hidayah (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
Vocabulary mastery is essential in language learning, particularly in Arabic, which features complex morphological and syntactic structures. However, vocabulary instruction ofte relies on memorization, limiting meaningful and sustained acquisition. This study examines the effectiveness of fill-in-the-blank sentence puzzles as a contextual instructional strategy to enhance vocabulary learning, retention, and learner engagement. A quasi-experimental design with a non equivalent control group was employed, involving 50 junior secondary students (25 experimental, 25 control). Data were collected through pretest, posttest, delayed posttest, an a motivation questionnaire. Quantitative data were analyzed using t-test and effect size calculations. The results show that the experimental group significantly outperformed the control group in both immediate learning (t(48) = 7.85, p < 0.001) and retention (t(48) = 6,92, p < 0.001). The experimental group also achieved higher retention (93.44% vs. 90.63%) and engagement (M = 88 vs. 72). These findings indicate that contextual puzzle-based tasks promote deeper cognitive processing and more durable vocabulary acquisition. This study provides emperical support for contextua; and task-based vocabulary learning and offers a practical, low-resource strategy for enhancing Arabic vocabulary instruction.